2017
DOI: 10.1214/17-ejs1237
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis testing of the drift parameter sign for fractional Ornstein–Uhlenbeck process

Abstract: We consider the fractional Ornstein-Uhlenbeck process with an unknown drift parameter and known Hurst parameter H. We propose a new method to test the hypothesis of the sign of the parameter and prove the consistency of the test. Contrary to the previous works, our approach is applicable for all H ∈ (0, 1). We also study the estimators for drift parameter for continuous and discrete observations and prove their strong consistency for all H ∈ (0, 1).The process X = {X t , t ≥ 0} is called a fractional Ornstein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…that is the same value for the covariance as in the right-hand side of (21). Concerning (iii), let us work with t ≥ s ≥ 0, since R H (t, s) is symmetric in t and s. We have to distinguish three cases.…”
Section: 42mentioning
confidence: 99%
“…that is the same value for the covariance as in the right-hand side of (21). Concerning (iii), let us work with t ≥ s ≥ 0, since R H (t, s) is symmetric in t and s. We have to distinguish three cases.…”
Section: 42mentioning
confidence: 99%
“…Remark 4.6. For 1 > t > s from (13) and (14) it follows that E(Z t − Z s ) 2 exponentially tends to zero as s → 1. It can be shown that all derivatives with respect to s of this expectation also tend to zero as s → 1.…”
Section: Probability Of Hitting Zero By the Fractional Ornstein -Uhlementioning
confidence: 99%
“…as T → ∞. Further, inserting (22) into (10), and applying the expansion (45) from Appendix A, we obtain…”
Section: Lemma 4 the Vector Of Main Components Of The Mle Has The Fomentioning
confidence: 99%